PENERAPAN METODE OPEN VPN-ACCESS SERVER SEBAGAI RANCANGAN JARINGAN WIDE AREA NETWORK PADA PT. VALDO INTERNATIONAL - Burhanuddin Burhanuddin; Mohammad Badrul (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2014)
The development of information technology has developed rapidly from year to year. The use of the Internet as a communication mediation in addition to very useful but still has flaws in its security. PT. Valdo International to build a computer network to facilitate the conduct of operations, such as Rejuvenation application systems and other purposes. we need a way to connect to the intranet access existing LAN network at headquarters and branch offices in order to be able to access data easily and safely. , Data information is not safe to be in the public network because it can be intercepted by unauthorized parties. Therefore PT. Valdo International build VPN (Virtual Private Network) using the PPTP MikroTik with lines and can perform other operations in private in the public network, with connections an economical and secure data security.